O25 The impact of COVID-19 lockdown on mental health and quality of life in patients with inflammatory arthritis. (26th April 2021) - Sweeney, Melissa; Carpenter, Lewis; de Souza, Savia; Chaplin, Hema; Tung, Hsiu; Caton, Emma; Galloway, James; Cope, Andrew; Yates, Mark; Norton, Sam
Abstract: Background/Aims COVID-19 lockdown has affected the mental health of many people around the world. People with inflammatory arthritis (IA) are at a higher risk of mental health and psychosocial consequences of the pandemic compared with the general population, since they are potentially more vulnerable to COVID-19 and experience higher rates of existing comorbid mental health disorder. Furthermore, vulnerable patients were advised to self-isolate for 12 weeks, which could further exacerbate emotional distress. This study aimed to explore the impacts of lockdown on mental health and wellbeing, and to determine which factors were associated with worse disease outcomes. Methods An online questionnaire was completed by 338 participants in the UK with an IA condition between June and July 2020. The questionnaire, designed with input from a service user, assessed various aspects of the impact of the pandemic on the quality of life of people with IA, including their mental health. Self-reported visual analogue scales (VAS) for patient global assessment (PGA) of disease activity, pain, fatigue, and emotional distress were completed relating to the previous week, and retrospectively for pre-lockdown (March) and early-lockdown (April). Specific mental health outcomes were further captured using the 8-item Patient Health Questionnaire (PHQ8) and the short UCLA loneliness scale. Linear regressions were conducted to determine mental health factors associated with worse outcomes on physical health measures (PGA, pain, and fatigue), controlling for fear of COVID-19 and COVID-19 status. Results Overall, 49% of participants met the PHQ8 criteria for moderate to severe depressive symptoms and 58% reported their mental health had worsened by more than 10 points on the emotional distress VAS during lockdown. Finally, 37% reported they were concerned about loneliness, with 26% indicating this had worsened during lockdown. Emotional distress VAS was significantly associated with PGA (b = 0.21, p < 0.01), pain (b = 0.24, p <0.01), and fatigue (b = 0.36, p <0.01). Similarly, depression was also associated with PGA (b = 0.95, p <0.01), pain (b = 0.92, p <0.01), and fatigue (b = 1.56, p <0.01). However, loneliness was not associated with any of the physical health VAS scores but was associated with the emotional distress VAS (b = 1.83, p =0.00). These results remained consistent for emotional distress, depression, and loneliness as predictors when accounting for fear of COVID-19 and COVID-19 status. Conclusion There has been a clear impact of the pandemic on the mental health of people with IA, and this should be taken into consideration by clinicians, especially as it appears to be related to worse overall reported physical health. The mixed results for loneliness in comparison to other mental health measures may illustrate the inter-relatedness of these aspects of mental and physical health, particularly in the context of lockdown. Disclosure M. Sweeney: None. L. Carpenter: None. S. de Souza: None. H. Chaplin: None. H. Tung: None. E. Caton: None. J. Galloway: None. A. Cope: None. M. Yates: None. S. Norton: None.